Analysis of The Impact of Political Connections and Ownership Structure on Corporate Performance (A Study on Companies Listed on BEI 2015-2019) - Zen, Fadia; Murdiono, Achmad; Istanti, Lulu Nurul; Pradana, Deni Bagas; Nofianti, Siska Krisdiana (CV. Proaksara Global Transeduka, 2024)
The aim of this study is to understand the differences in the impact of government and political connections, considering various ownership structures, leverage, and company size, on corporate performance. Focusing on political connections during the Jokowi regime, we analyze based on 2843 observations of companies listed in Indonesia. Additionally, we use OLS regression and address endogeneity problems with Robust Standard Error, resulting in new regression outcomes free from endogeneity issues. Our findings indicate that in the Jokowi regime, political connections significantly enhance corporate performance. Furthermore, the business landscape in Indonesia is dominated by conglomerates, family-owned businesses, and politicians. These findings can assist regulators and standard setters in considering future ownership structures, especially in state-owned enterprises, tender restrictions, and good corporate governance supervision, helping to devise the best strategies to improve welfare and reduce the excessive control of conglomerates in Indonesia. Instead of incremental work, this study focuses on corporate performance from a broader dimension of political connections, also examining the influence of other variables central to numerous research studies.